Teachers ' Moral Motivation for Peace Education among Herder-Farmer Adult Communities in Tanzania - Mngarah, Daniel Mbonea (Papers in Education and Development, 2021)
This article presents findings of the study on teachers ' moral motivation for implementing peace literacy among herder-farmer adult communities which are characterised by hostilities in Tanzania. The study objectives were twofold namely, to: determine teacher readiness factors for implementing peace literacy among the differing adult communities and; identify the potential moral content supporting peace-building processes for the respective communities. The study involved thirteen teachers from three primary schools and one ward secondary school, employing semi-structured interviews and documentary review methods to generate data. Data were subjected to content analysis and provided themes that generated pertinent meanings made by informants. Results established that several factors influenced teachers ' readiness to implement peace literacy, and established other moral ' literacies ' relevant to adults from those communities. Keywords: adult learners, adult literacy, self-determination theory, transformative learning theory, transformative pedagogy